Rock Paintings in Jizzakh Oasis - Shokhrukh Jonuzokov (European Science Publishing, 2023)
This article provides information on the study of the rock paintings of the Jizzakh oasis, the research conducted by archaeologists on the study, the formation of rock paintings and the factors that caused it.
Keywords: Jizzakh oasis, rock paintings, archeological excavations, results of scientific research, research.